English language reform and the process of democratic change - James Campbell, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2009)
Malaysian society has and is undergoing considerable social, political, economic and educational change. Scholars point to the forces of globalization and the needs to be able to meet the challenges of globalization as the central driver of language policy. Commentators, academics and many in the general public have focused on the need for Malaysia to adapt to globalization and the importance of English to this process given the needs and characteristic of the knowledge economy. However, there appears to be less recognition of the way such a change in Malaysian language policy needs to be engaged in a dynamically shifting knowledge society and developing public sphere. Language is a social act and the debate over language and its place and role in society is therefore a debate over the nature and quality of social interaction. Debate over language is thus inherently political. Due to the growth and development of an interactive and engaged public sphere and knowledge society in Malaysia, there is a need to approach to the idea of engaging English that grasps the plurality and complexity of its role in the world. The political approach to engaging English in Malaysia needs to engage democratic deliberation in a society that is increasingly fragmented but also showing signs of developing an active public sphere not beholden to top down authority. Disagreement over language and the way the debate is theorized hides from view the possibility of points of consensus on the issue of English language and Malaysian education. Establishing overlapping consensus through public deliberation and consultation is a necessary precondition to effective language policy in contemporary Malaysia. Failure to understand this only leads to policy paralysis.